Cortical Excitability and Connectivity in Patients With Brain Tumors - Rizzo, Vincenzo; Terranova, Carmen; Raffa, Giovanni; Cardali, Salvatore Massimiliano; Angileri, Filippo Flavio; Marzano, Giuseppina; Quattropani, Maria Catena; Germanò, Antonino; Girlanda, Paolo; Quartarone, Angelo (Frontiers in Neurology, 2021)
Background: Brain tumors can cause different changes in excitation and inhibition at neuronal network level. These changes can be generated from mechanical and cellular alterations, often manifesting clinically as seizures. Objective/Hypothesis: The effects of brain tumors on cortical excitability have not yet been well evaluated. The aim of current study was to further investigate cortical-cortical and cortical-spinal excitability in patients with brain tumors using a more extensive TMS protocol. Methods: We evaluated cortical excitability on 12 consecutive patients with lesions within or close to the precentral gyrus, as well as in the subcortical white matter motor pathways. We assessed resting and active motor threshold (RMT e AMT), short-latency intracortical inhibition (SICI), intracortical facilitation (ICF), short-latency afferent inhibition (SAI), long-latency afferent inhibition (LAI), cortical silent period (CSP) and interhemispheric inhibition (IHI). Results: Cortical excitability was reduced in patients with brain tumors than in healthy control. In addition SICI, ICF and SAI were lower in the affected hemisphere compared to unaffected and healthy control. Conclusions: Cortical excitability (CE) is abnormal in hemispheres affected by brain tumors. Further studies are needed to determine if CE is related with motor impairment.